Structures of collagen IV globular domains: insight into associated pathologies, folding and network assembly. Corrigendum. (2020) - Casino, Patricia; Gozalbo-Rovira, Roberto; Rodrıguez-Dıaz, Jesus; Banerjee, Surajit; Boutaud, Ariel; Rubio, Vicente
No abstract available